Effectiveness of Four Different Light-activated Composites Cure with Different Light Energy Densities (Mustansiria Dental Journal, 2018)
Background: This study investigated the influence of light energy density (intensityx time) on the effectiveness of composite cure in view of the curing profiles of lightpolymerizationunits with different light- activated composites to determine theenergy density that satisfies adequate polymerization of all light-activatedcomposites types used in this study.Materials and methods: This study investigated the hardness of the top/bottomsurfaces and hardness ratio of 2-mm thick composite specimens after exposure todifferent light energy densities. Parameters included five light intensities (200, 300,400, 500 and 600 mW/cm2) and seven curing times (20, 40, 60, 90, 120, 150 and180 seconds) for each of the four different light-activated composite materials(Tetric Ceram, Heliomolar, Herculite XRV and Degufill Mineral).Results: Statistical analysis of the data by using the one-way analysis of variancerevealed that, most of the hardness ratios exhibited a very highly significantdifference according to intensity, composite type and curing time. The resultsindicated that, Heliomolar and Degufill Mineral light-activated composites requiredapproximately (36 J/cm²) energy density for adequate polymerization for a 2-mmthick specimen while, Herculite XRV and Tertric Ceram light-activated compositesrequired approximately (12 J/cm²) energy density for adequate polymerization for a2-mm thick specimen.Conclusion: This study indicated that, final curing should not be done with energydensity less than (300 mW/cm2 for 120 seconds, 400 mW/cm2 for 90 seconds and600 mW/cm2 for 60 seconds) for Heliomolar and Degufill Mineral light-activatedcomposites.